Strain mapping in symmetrical core-shell gold nanorods from HRTEM images. (November 2021) - Zhang, Hui; Zhang, Ran; Geng, Yongfeng; Ji, Yinglu; Zhang, Yi; Li, Xu; Meng, Dejing
Abstract: Strain distribution, interface type and the causes of strain in gold core-shell nanorods were studied by employing high-resolution electron transmission microscope (HRTEM) and Geometric Phase Analysis (GPA). Anisotropic Strain distributions in gold core-shell nanorods were affected by l -cysteine (Cys) concentration and AA/Au 3+ ratio which determines shell growth kinetics. Strain circles were generated at the core-shell interfaces of gold nanorods. The 002 strain distributions of gold nanorods were very sensitive to the increase of Cys concentration and AA/Au 3+ ratio. Strain distributions with high strain values on 111 planes were more significant than that on 002 planes. This state was related to the preferential adsorption of thiols on 111 planes. The core-shell interface of gold nanorods was determined to be a mix of distorted coherent interface and semi-coherent interface, which was mainly produced via the slip of 111 planes along <110> slip direction. The gold shell covered the whole core at the growth conditions of different Cys concentrations and AA/Au 3+ ratios provided in this work via seed-mediated symmetric epitaxial growth. The strain at the core-shell interface was mainly generated by Au–S bonds and lattice distortion. Graphical abstract: Image 1 Hightlights: The strain of the core-shell gold nanorods was affected by l -Cysteine concentration and AA/Au 3+ ratio. 111 strain was more sensitive than 002 strain to the change of synthesis conditions. The gold nanorod core-shell interface was a mix of distorted coherent interface and semi-coherent interface. Shell growth was attributed to seed-mediated epitaxial growth with symmetry. Au–S bonds and lattice distortion were the main causes of strain at the core-shell interface.